Physical Anthropology : The Essentials - Jurmain, Robert; Jurmain, Robert (Australia : Wadsworth, 2013)
PHYSICAL ANTHROPOLOGY: THE ESSENTIALS, 9E, International Edition, presents a concise and authoritative introduction to physical anthropology with the goal of helping students understand why it is important to know about human evolution by showing how humans are biologically connected to all other life. These biological connections link our species with our ancient ancestors, our contemporary primate cousins, and show how closely modern human populations are related to each other. The text has been reframed to emphasize this theme of biological connections as well as the connections between chapters in the material presented. This new framework will better help students grasp the big picture of human evolution and better navigate the material. Supported by new chapter opening Learning Objectives, new visual diagrams (see Chapter One)and other summation pedagogy such as "What's Important" boxes that put key chapter concepts into perspective for students, this text continues to help students master basic biological principles of physical anthropology and so be able to better understand human origins and our place in the biological world. Altogether, PHYSICAL ANTHROPOLOGY: THE ESSENTIALS, 9E, International Edition integrates coverage of the latest finds with relevant technologies to be the most up-to-date text available.
Includes Glossary 399-404p.; Bibliography 405-416p.; Index 417-431p.
Keywords: Modern human biology; Physical anthropology; Premodern humans; Anthropology